Corporate governance and earnings management in Malaysian government linked companies: the impact of GLCs transformation policy - Mohamad, Muslim Har Sani; Ab Rashid, Hafiz-Majdi; Ali Mohammed Shawtari, Fekri (Emerald, 2012)
Purpose – As the major shareholder, in 2004, the Malaysian Government embarked on the transformation initiative of the Government Linked Companies (GLCs). One of the main initiatives was to enhance board effectiveness through its Green Book. Soon after, the progress performance review revealed that the GLCs reported improved earnings. Such drastic performance turnarounds triggered the question as to whether earnings quality is at stake. The purpose of this paper is to examine the impact of the tightening of corporate governance mechanisms on earnings management (EM) activities of the GLCs.